Bipolar disorder at mixed states and major depressive disorder with mixed features differ in peripheral biochemical parameters - Xiaohui Wu; Shuo Wang; Zhiang Niu; Yuncheng Zhu; Ping Sun; Wenxi Sun; Jun Chen; Yiru Fang (BMC Psychiatry)
Abstract Background Little is known about the peripheral biochemicals between bipolar disorder at mixed episodes (BDM) and major depressive disorder with mixed features (MDM). This retrospective study was aimed to compare the peripheral biochemical parameters between patients with BDM and MDM. Methods This study included data from 269 BDM patients and 86 MDM patients. Biochemical markers covering immune-inflammatory, liver function, metabolic, and thyroid hormone indices were analyzed. Logistic regression models were employed to evaluate associations between biochemical markers and diagnosis. Network analysis and Principal Component Analysis (PCA) was also performed to investigate the relationships among these parameters. Results BDM patients had higher neutrophil percentage (NEUT%), white blood cell count (WBC), free triiodothyronine (FT3) and free thyroxine (FT4), while MDM patients exhibited higher levels of C-reactive protein (CRP), direct bilirubin (DBIL) and prealbumin (PA). NEUT%, WBC, FT3 and FT4 showed positive association with the diagnosis of BDM, while PA and DBIL displayed negative correlation with BDM. No significant differences in either network structure or global strength were found between BDM and MDM groups. Conclusion Peripheral biochemical markers, particularly those related to the immune-inflammatory factors and thyroid hormones, differ between BDM and MDM, which could contribute to better understanding of potential status mechanism under the disorders. Trial registration International Clinical Trials Registry Platform: NCT03949218. Registered on 13/05/2019.